Tinjauan Hukum Islam Pemanfaatan Tanah PT. KAI oleh Masyarakat Perspektif Maqashid Syariah dan Kesejahteraan Ekonomi - Syaripudin, Enceng Iip; Mubarokah, Ismi Latifah (STAI Al Musaddadiyah Garut, 2025)
The utilization of land owned by PT Kereta Api Indonesia (PT KAI) that is not being used as intended is still commonly found in various regions. This situation gives rise to numerous issues, both in terms of positive law and from the perspective of Islamic law. The aim of this research is to examine the mechanisms by which the community utilizes such land and to analyze it through the lens of maqashid shariah, economic welfare aspects, and the fundamental principles of Islamic law.The method used in this study is a qualitative approach with a literature review methodology. Data sources were obtained from various references, including national academic journals, undergraduate theses, books, and online articles accessed via Google Scholar.The findings reveal that the process of utilizing PT KAI land by the community involves several administrative steps, including the submission of a formal request letter, asset data verification, field surveys, lease contract signing, as well as payment and handover of the leased property.From the perspective of maqashid shariah, this utilization aligns with the five primary objectives of Islamic law: protection of religion, life, intellect, lineage, and property. Meanwhile, the analysis of economic welfare includes variables such as population, education, income, household consumption, employment, and housing and environmental conditions. In the view of Islamic law, this practice is analyzed based on principles such as tawhid (oneness of God), justice, consultation (shura), mutual assistance, equality, tolerance, and enjoining good while forbidding evil (amar ma’ruf nahi munkar). Therefore, the community’s use of PT KAI’s land assets should be comprehensively understood in order to achieve social justice, collective benefit (maslahah), and legal certainty. Keywords: Land utilization, maqashid shariah, economic welfare, Islamic law